Heart rate variability is depressed in the early transitional period for newborns with complex congenital heart disease - Mulkey, Sarah B. (Clin Auton Res, 2019)
PURPOSE: To compare early changes in autonomic nervous system (ANS) tone between newborns with complex congenital heart disease (CHD) and newborns without CHD. METHODS: We performed a case–control study of heart rate variability (HRV) in newborns with complex CHD [transposition of the great arteries (TGA) or hypoplastic left heart syndrome (HLHS)] and low-risk control newborns without CHD. Cases with CHD were admitted following birth to a pediatric cardiac intensive care unit and had archived continuous ECG data. Control infants were prospectively enrolled at birth. ECG data in cases and controls were analyzed for HRV in the time and frequency domains at 24 h of age. We analyzed the following HRV metrics: alpha short (α(s)), alpha long (α(L)), root mean square short and long (RMS(s) and RMS(L)), low-frequency (LF) power, normalized LF (nLF), high-frequency (HF) power, and normalized HF (nHF). We used ANOVA to compare HRV metrics between groups and to control for medication exposures. RESULTS: HRV data from 57 infants with CHD (TGA, n = 33 and HLHS, n = 24) and from 29 controls were analyzed. The HRV metrics α(S), RMS(L), LF, and nLF were significantly lower in infants with CHD than in the controls. Due to the effect of normalization, nHF was higher in CHD infants (P < 0.0001), although absolute HF was lower (P = 0.0461). After adjusting for medications, α(S) and nLF remained lower and nHF higher in newborns with CHD (P  < 0.0005). CONCLUSIONS: Infants with complex CHD have depressed autonomic balance in the early postnatal period, which may complicate the fetal–neonatal transition.